Using Biofacies Analysis of a Tertiary Algal Reef (Pinnacle Reef - Middle Eocene IIA), at Burton Guyot (IODP Site U1376) to Determine Transition from Greenhouse to Icehouse - Khameiss , Belkasim; Fluegeman , Richard; Hoyt , William (Scientific Journal of University of Benghazi, 2023)
Twenty-five samples were collected at 30 cm intervals from the studied cored interval within the limestone unit (AII) reported at IODP Site U1376 on Burton Guyot. The purpose of this research is to examine and identify the coral and algae suites in the studied core concerning sea level fluctuation during the Eocene time. This reef is isolated by being between two volcanic units in the Southwest Pacific Ocean. Eleven biofacies units have been established based on the fabric of the grains. The biofacies units are as follows; Algal-coral grainstone, foraminiferal algal-coral grainstone (Alabaminabed), foraminiferal algal-coral packstone to grainstone (Heterostegina bed), algal-coral grainstone, foraminiferal algal boundstone, foraminiferal algal grainstone (Lagena bed), foraminiferal algal grainstone (Cibicidoides micrus-bed), foraminiferal algal boundstone to grainstone, foraminiferal algal-coral grainstone, algal echionoidal packstone, and foraminiferal algal coral wacke-packstone. This is the first study to use both algae and coral in differentiating the units mentioned above. The only coralline red algae recognized in the samples is Lithothamnion camarasae. This species is a good indicator of the warm climatic conditions during the middle-late Eocene. The only species of coral found in these units is Isopora togianensis, a scleractinian reef builder. The high percentage of algae compared to coral indicates a climatic change from a greenhouse to an icehouse climate. The faunal trend during this time also indicates a tectonic change.